Effectiveness of Nursing Discharge Planning Interventions for Stroke Patient: A Systematic Review - Indrawati, Lilis; Fitryasari, Rizki; Ahsan, Ahsan (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Inadequate discharge planning for stroke patients poses significant challenges for healthcare. Effective discharge planning interventions have been examined in several studies, but little information is available about nursing roles or specific components of these interventions. It aims to explain the effectiveness of nursing planning interventions for stroke patients. This study was conducted through a systematic review with the PRISMA approach. We obtained 28 articles, and 15 were considered relevant. To analyze the methodological quality in each study, JBI was used for this type of experimental study. Based on a review of 15 articles, it was found that family empowerment-based discharge planning was proven to be effective in improving quality of life, self-care independence, exercise-based discharge planning to be effective in self-care independence, and discharge planning based on home visits and ADL training to be effective in improving self-care independence and mobility.